Konsep dan Urgensi Kemandirian Lembaga Keimigrasian Indonesia - Eka Martina Wulansari (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
In safeguarding the strategic geographical area of Indonesia for security and defense, the immigration sector plays a pivotal role. This role is crucial in protecting the diverse interests of the Republic of Indonesia, particularly in terms of security and prosperity. To effectively support these interests with foreign parties, government institutions require efficient and effective legal instruments in the immigration domain. However, the immigration function, currently under the Directorate General of Immigration at the Ministry of Law and Human Rights, faces challenges due to bureaucratic complexities, resulting in a perceived sluggishness in its implementation.In the era of globalization, there is an urgent need for an independent immigration agency outside the Ministry of Law and Human Rights. This agency, directly responsible to the President, is envisioned to enhance the implementation of the immigration function, particularly in efficiently monitoring the influx of foreigners. The revision of Law Number 6 of 2011 concerning Immigration provides the legal foundation for establishing an independent immigration institution in Indonesia directly accountable to the President.This writing, utilizing the normative legal writing method, aims to explore and analyze the necessity and structure of an independent Indonesian immigration agency. The focus is on optimizing the functions, duties, and authorities of immigration, aligning them with the demands of the globalization era.